Characterization of ruminal bacteria in grazing Nellore steers - Barbetta-de-Jesus, Raphael; Granja-Salcedo, Yury T.; Messana, Juliana D.; Takeshi-Kishi, Luciano; Macedo-Lemos, Eliana Gertrudes; Marcondes-de-Souza, Jackson Antonio; Teresinha-Berchielli, Telma (Revista Colombiana de Ciencias Pecuarias, 2019)
Background: Rumen microorganisms have developed a series of complex interactions, representing one of the best examples of symbiosis between microorganisms in nature. Conventional taxonomic methods based on culture techniques are being replaced by molecular techniques that are faster and more accurate. Objective: To characterize rumen bacterial diversity of Nellore steers grazing on tropical pastures by sequencing the 16S rRNA gene using Illumina sequenctng. Methods: Three rumen-cannulated Nellore steers were used. The liquid and solid fractions of the rumen contents were processed to extract metagenomic DNA, and the VI and V2 hypervariable regions of the 16S rRNA gene were sequenced using Illumina sequencing. Results: A total of 11,407,000 reads of adequate quality were generated, and 812 operational taxonomic units (OTUs) were found at the species level. Twenty-seven phyla were identified, and the predominant phyla were Firmicutes (23%), Bacteroidetes (14%), Proteobacteria (10%), Spirochaetes (9%), Fibrobacteres (7%), Tenericutes (5%), and Actinobacteria (2%), which represented 70% of the total phyla identified in the rumen content. Conclusion: Rumen environment in grazing Nellore steers showed high bacterial diversity, with Firmicutes, Bacteroidetes, Proteobacteria, Spirochaetes, and Fibrobacteres as the predominant phyla.